Participação, mulheres e práticas cotidianas : um estudo nos conselhos e conferências de saúde em Aracaju/SE - Alexandre, Virginia Caroliny Silva (2019)
The study aims to discuss the participation process in the Brazilian Public Health System. The research fieldwork has been based on attending the Health Councils’ meetings in the primary health care level and in the Health Conferences in the Municipality and State levels in the State of Sergipe. The methodological approach was inspired by an ethnographic process of research. The research examines two kinds of democratic processes, the first being the policies and rules established that set up procedures and processes for participation and the second, the everyday processes of participation through people’s participation in their local communities. We have collected interviews, photos and videos. Participation in these institutions was a locus of interests of power and political control. On the other hand, in everyday practices, it seems that people are reinventing ways to articulate forms of participation to increase the value of health care service in their community. The study has shown that women are more participative, especially in the primary health care levels, which deals with their local needs. The research also has shown that the institutional places for participations is where it less happens effectively. Participation process happens much more in everyday lives then in those places organized by the government managements._________________________________________________________________________________________